2014
DOI: 10.3390/bs4040487
|View full text |Cite
|
Sign up to set email alerts
|

Network of Spaces and Interaction-Related Behaviors in Adult Intensive Care Units

Abstract: Using three spatial network measures of “space syntax”, this correlational study describes four interaction-related behaviors among three groups of users in relation to visibility and accessibility of spaces in four adult intensive care units (ICUs) of different size, geometry, and specialty. Systematic field observations of interaction-related behaviors show significant differences in spatial distribution of interaction-related behaviors in the ICUs. Despite differences in unit characteristics and interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 25 publications
5
23
0
Order By: Relevance
“…However, designers’ interpretations of communication requirements are different from the users’ perceptions, and this makes consensus about design optimization complicated (Trzpuc and Martin, 2010). Similar to the findings of Rashid et al (2014), the data analysis in this study indicated that departments with lower visibility were associated with a higher amount of walking to seek interactions and communication while standing. Also, there is another consistency with the existent literature as interactions are more concentrated in the main nurse station in a centralized unit (Ritchey and Pati, 2008; Zborowsky et al , 2010).…”
Section: Discussionsupporting
confidence: 83%
“…However, designers’ interpretations of communication requirements are different from the users’ perceptions, and this makes consensus about design optimization complicated (Trzpuc and Martin, 2010). Similar to the findings of Rashid et al (2014), the data analysis in this study indicated that departments with lower visibility were associated with a higher amount of walking to seek interactions and communication while standing. Also, there is another consistency with the existent literature as interactions are more concentrated in the main nurse station in a centralized unit (Ritchey and Pati, 2008; Zborowsky et al , 2010).…”
Section: Discussionsupporting
confidence: 83%
“…A body of research has identified design factors that affect face-to-face communication and interactions in various settings. For instance, more frequent communication was reported in spaces with more integrated overall layout [31][32][33], in workspaces with accessible shared team spaces [18,34,35], and in locations that are more accessible to all other spaces [36]. Furthermore, more frequent face-to-face interactions were reported among individuals in close physical distance, such as those who were on the same floor or corridor [37], co-located in the same space [16,38], and proximate to each other's workstations [19,20].…”
Section: Communicationmentioning
confidence: 99%
“…The studies in this category are discussed in two groups -studies in one of these groups investigate the effects of layouts on behaviors by comparing the differences in carefully selected unit layouts (Carlson et al, 2006;Freeman and Smalley, 1968;Hendrich et al, 2008;Jaco, 1972;Nuffield Report, 1956;Shepley and Davies, 2003;Thomas & Goldin, 1975;Whitehead et al, 1984;Yi and Seo, 2012), while the studies in the other group uses space syntax techniques to investigate the effects of layouts on behaviors (Cai and Zimring, 2012;Choudhary et al, 2010;Hendrich et al, 2009;Lu et al, 2009;Rashid et al, 2012;Sagha Zadeh et al, 2012).…”
Section: Studies Involving Behaviors and Unit Layout Featuresmentioning
confidence: 99%
“…Studies involving behaviors and unit layout features. The studies in this category are discussed in two groups -studies in one of these groups investigate the effects of layouts on behaviors by comparing the differences in carefully selected unit layouts (Carlson et al, 2006;Freeman and Smalley, 1968;Hendrich et al, 2008;Jaco, 1972;Nuffield Provincial Hospitals Trust & University of Bristol, 1956;Shepley and Davies, 2003;Thompson and Goldin, 1975;Whitehead et al, 1984;Yi and Seo, 2012), while the studies in the other group uses space syntax techniques to investigate the effects of layouts on behaviors (Cai and Zimring, 2012;Choudhary et al, 2010;Hendrich et al, 2009;Lu et al, 2009;Rashid et al, 2012;Sagha Zadeh et al, 2012). Among the early comparative studies, Freeman and Smalley (1968) used personal travel time of medical and surgical patients to explain how the position of substations, monitoring devices and the number of patients affect the amount of travel.…”
Section: Research Studies With Psychotechnical Orientationmentioning
confidence: 99%
See 1 more Smart Citation